Supraspinous Fossa: Anatomy and Pathology - Saran, Sonal; Shirodkar, Kapil; Gavvala, Sai Niharika; Evans, Scott; Iyengar, Karthikeyan P.; Jevalle, Devina Ghoorah; Botchu, Rajesh (Indian Journal of Radiology and Imaging, 2024)
Supraspinous fossa is an important location in the periscapular region, which houses important structures such as the supraspinatus muscle and the suprascapular nerve. The supraspinous fossa can be affected by pathologies involving its contents (supraspinatus muscle and suprascapular nerve), osseous boundary (scapular body, distal clavicle, and spinous process), or superficial soft tissue covering it. In this pictorial review, we describe the detailed anatomy of the supraspinous fossa. We have also covered imaging of wide range of pathologies that can affect supraspinous fossa such as paralabral cyst, muscle edema/atrophy, malignancies (primary and secondary), and miscellaneous lesions (myositis ossificans, fibromatosis, nerve sheath tumor, etc.). An awareness of the imaging findings of these entities is essential for a radiologist to avoid misinterpretation and can aid a timely diagnosis.
Keywords: supraspinatus muscle; suprascapular nerve; ultrasonography; MRI